Keadilan Sosial dan Hak Kewarganegaraan: Kebijakan Publik dalam Bidang Pendidikan - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Anastasya Egita Putri; Nabila Siti Ngaisyah; Zulfa Nur Bahirah (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
The education system in Indonesia comprises a series of interconnected components and educational activities aimed at achieving national education goals. With the growing demands for educational reform, policies related to education have undergone several modifications. Every individual in the country has the right and obligation to attain a decent life; however, in reality, many are still unable to experience genuine well-being. This situation arises because the government and leaders tend to prioritize rights over fulfilling their responsibilities. The methodology employed is qualitative, The research findings indicate that the education policies implemented have not yet fully reached all segments of society, particularly vulnerable groups, despite the presence of public participation in forums such as Musrenbang. Moreover, the success of implementation largely depends on effective coordination between central and regional governments, as well as adequate socio-political support.